THE INFLUENCE OF DER, ROE AND EPS ON STOCK PRICES IN FINANCIAL SECTOR COMPANIES LISTED ON THE IDX IN 2019 - Tresnawati, Mei; Fauzi, Achmad; Mardi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This research aims to determine influence of debt to equity ratio, return on equity and earnings per sharetoward stock price, either partially or simultaneously. This research conduct in financial sector companieslisted in BEI period 2019. The affordable population in this research consist of amount to 85 companiesand sample used many as 52 companies by using simple random sampling. The data used aresecondary data collected were analyzed using multiple linear regression. Based on the results of thediscussion it is concluded that the multiple linier regression equation obtained is Y = 6,313 + 0,047X1+ 0,399X2 + 0,272X3. The results of analysis show: (i) there is no significant positive influence betweenDER with stock price, (ii) there is significant positive influence between ROE and stock price, (iii) there issignificant positive result between EPS and stock prices. And basic on the result of the analysis is thatDER, ROE and EPS stimultaneously affect stock price.